2009
DOI: 10.1016/j.sjbs.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of azadirachtin of neemix-4.5 on SWR/J mice

Abstract: Inbred normal SWR/J male and female mice, 8-10 weeks old and weighing 22.55-26.72 g, were used throughout the study. A total of 100 males and 100 females were used and were divided into 20 groups, 10 animals in each group. Azadirachtin of neemix-4.5, a commercial botanical pesticide derived from the neem tree, orally administered to male and female SWR/J mice at a dose level 9.0 mg/kg (1/10 LD50) for different treatment periods (2, 4, 6, 8 or 11.5 weeks) has produced signs of toxicity, mortality and changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Also, there were increases in packed cell volume (PCV), mean corpuscular hemoglobin (Hb) concentration, red blood corpuscles (to check the level of anemia), white blood cells, and lymphocyte counts, but no cytotoxic effects were observed. In another study carried out by (Abou-Tarboush, et al [50]), it was found that azadirachtin was orally administrated to male and female SWR/J mice at a dose level of 9.0 mg/kg (1/10 LD 50 ) for different treatment periods has produced signs of toxicity, mortality, and changes in the body, histopathological changes in the livers, kidneys and testis and tissue weights of both sexes at almost all treated periods. The present study showed a significant reduction in creatinine levels on certain days after treatment or recovery period as indicators for renal injury induced by neem formulation treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there were increases in packed cell volume (PCV), mean corpuscular hemoglobin (Hb) concentration, red blood corpuscles (to check the level of anemia), white blood cells, and lymphocyte counts, but no cytotoxic effects were observed. In another study carried out by (Abou-Tarboush, et al [50]), it was found that azadirachtin was orally administrated to male and female SWR/J mice at a dose level of 9.0 mg/kg (1/10 LD 50 ) for different treatment periods has produced signs of toxicity, mortality, and changes in the body, histopathological changes in the livers, kidneys and testis and tissue weights of both sexes at almost all treated periods. The present study showed a significant reduction in creatinine levels on certain days after treatment or recovery period as indicators for renal injury induced by neem formulation treatments.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that azadirachtin acts on the mitotic cells and blocks the microtubule polymerization [3]. The antiproliferating effect of azadirachtin is due to blocking of cell cycle and induction of apoptosis [1]. It has been suggested that azadirachtin is highly reactive and have many cellular molecules as target in cytoplasm as well as in nucleus [16].…”
Section: Introductionmentioning
confidence: 99%